Clinical Study of Severe Cutaneous Adverse Reactions to Drugs - Debajit Das; Shahjubin Basir (International Journal of Pharmaceutical and Clinical Research, 2023)
Background: Adverse drug reaction is defined as ‘an undesirable clinical manifestation resulting from administration of a particular drug; this includes reaction due to overdose, predictable side effects and unanticipated adverse manifestations’. 1 of every 1000 hospitalized patients has a serious cutaneous drug reaction. SJS and TEN are associated with severe morbidity and mortality. The fatality rate in SJS is reported to be 5-10%, while in TEN it is reported to be 25-30%. So, the following study shall thus be a sincere effort to explore more about the adverse drug reactions. Objectives: To study the different clinical patterns of SCAR, and to identify the offending drugs causing different types of SCAR. Methods: The study has been conducted in the department of Dermatology, Silchar Medical College & Hospital, and Silchar, Assam over a period of one year extending from 1 st June 2018 to 31 st May 2019 after approval from the Institutional Ethics Committee (IEC) and after obtaining informed consent from the patients. Results: Out of the total 57,712 new patients attending the Department of Dermatology, Silchar Medical College & Hospital, and Silchar during the period from 1 st June 2018 to 31 st May 2019, 31 patients were diagnosed as having severe cutaneous adverse reactions due to drugs. Out of a total of 31 patients, 18 patients (58.06%) were male, while 13 patients (41.94%) were female with a male: female ratio of 1.38:1. In this study, the most common clinical pattern was the SJS-TEN part of the spectrum (64.52%) with SJS 35.48%, SJS/TEN overlap 6.45%, TEN 22.58%. In present study, Antimicrobials were the most common causative drugs (41.93%) followed by Anticonvulsants (35.48%) followed by Antipyretic analgesics (16.13%). The most common drug causing SCAR in this study was Carbamazepine (22.58%).The duration from the drug administration to cutaneous reactions (Reaction time) ranged from 12 hours to 60 days in this study. Shorter duration of 12 hours was seen in 1 case of TEN associated with ...